REPRESENTATIONS OF HYBRIDIZATION IN ANCIENT IRAQI ART - Asraa Mehdi Chechan, Prof Dr. Salwa Mohsin Hameed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The aim of this paper is (to identify the representations of hybridization in ancient Iraqi art). Where the limits of the research were limited to studying the representations of hybridization in the ancient Iraqi art of the period (3500 BC - 539 BC).It contains a study of the meaning of crossbreeding and ancient doctrines in Mesopotamia. As well as representations of hybridization in the ancient Mesopotamian arts. Access to the indicators of the theoretical framework. This research included research procedures, and defining the research community and the selection of the sample models, which amounted to (3) models. The results were represented by the topic of crossbreeding by relying on the mythical narration of the concept of hybridization, its meanings and connotations with intellectual references as well as in the specificity of each model.